Janet Ward
New member
- Joined
- Sep 6, 2010
- Messages
- 8
I am lost solving logarithmic equations.
here is an example hopefully you can tell me where I'm going wrong
logx + log(x-1) = log(4x)
logx(x-1) = log(4x)
log (x^2 -x) - log(4x) = 0
log (x^2 - 5x) = 0
x^2 -5x = 1 because 10^0=1
x^2-5x-1=0 now I'm not sure what to do.
here is an example hopefully you can tell me where I'm going wrong
logx + log(x-1) = log(4x)
logx(x-1) = log(4x)
log (x^2 -x) - log(4x) = 0
log (x^2 - 5x) = 0
x^2 -5x = 1 because 10^0=1
x^2-5x-1=0 now I'm not sure what to do.